Cucurbitaceae COld Peeling Extracts (CCOPEs) Protect Plants From Root-Knot Nematode Infections Through Induced Resistance and Nematicidal Effects - De Kesel, Jonas; Degroote, Eva; Nkurunziza, Radisras; Singh, Richard Raj; Demeestere, Kristof; De Kock, Karen; Anggraini, Riska; Matthys, Jasper; Wambacq, Eva; Haesaert, Geert; Debode, Jane; Kyndt, Tina (Frontiers in Plant Science, 2022)
With nematicides progressively being banned due to their environmental impact, an urgent need for novel and sustainable control strategies has arisen. Stimulation of plant immunity, a phenomenon referred to as ‘induced resistance’ (IR), is a promising option. In this study, Cucurbitaceae COld Peeling Extracts (CCOPEs) were shown to protect rice (Oryza sativa) and tomato (Solanum lycopersicum) against the root-knot nematodes Meloidogyne graminicola and M. incognita, respectively. Focusing on CCOPE derived from peels of melon (Cucumis melo var. cantalupensis; mCOPE), we unveiled that this extract combines an IR-triggering capacity with direct nematicidal effects. Under lab conditions, the observed resistance was comparable to the protection obtained by commercially available IR stimuli or nematicides. Via mRNA sequencing and confirmatory biochemical assays, it was proven that mCOPE-IR in rice is associated with systemic effects on ethylene accumulation, reactive oxygen species (ROS) metabolism and cell wall-related modifications. While no negative trade-offs were detected with respect to plant growth or plant susceptibility to necrotrophic pests or pathogens, additional infection experiments indicated that mCOPE may have a predominant activity towards biotrophs. In summary, the presented data illustrate a propitious potential for this extract, which can be derived from agro-industrial waste streams.